Jürgen Habermas and the dilemmas of experience of disability - Pezdek, Krzysztof (Nursing philosophy, 2017)
The article addresses Jürgen Habermas’ theory of communicative action, which offers very productive tools for analysing disability. The Habermasian division of social reality helps examine positive and negative effects of tensions between the lifeworld of a person with disability and the system. By exploring such an individual's communicative action, one can obtain an insight into his/her validity claims and disruptions in the communication process and self-understandings inscribed in group narratives. The study reported in the article used in-depth interviews, which narratively reveal the experiences of a person with disability in family, education, sports and labour. The key findings are, first, that the rationalization of lifeworlds of people with disability increases while processes in which they are colonized by the system intensify; second, that education and family are significant factors in the raising of validity claims; and third, that validity claims as tools of verbal communication should be augmented with arguments from non-verbal language (e.g. gesture, empathy).